Efficacy: Can It Improve Students' Learning Achievement - Octhian, Sarah Gracenda Aflah; Hura, Rosnila (Jurnal Pendidikan Agama Kristen (JUPAK), 2024)
Education is one of the needs that is needed by every individual and is a very important thing, because education has an important role and has a big impact on human life. In the world of education, of course, it cannot be separated from various problems which certainly require an answer as a solution to existing problems. One of the topics of discussion in the world of education at this time is regarding the nature of self-efficacy or self-efficacy that exists in students. According to several journals, several studies have been conducted on self-efficacy in students and the results found that self-efficacy has a significant impact on students, both in terms of thinking patterns, ways of learning and doing assignments, and influencing student learning outcomes. In addition, self-efficacy plays an important role for each individual, so that they are able to discover and develop their potential (Rustika 2012). Even though this self-efficacy has a positive impact on student learning outcomes, in reality not all students have this self-efficacy themselves. Because of that, another party is needed to generate self-efficacy in a student. Therefore, this paper discusses "Self efficacy: can it increase student achievement?"